Urbanization: definition, components, and classification in context of land and economics sciences - Nazarenko, V. (Land Management, Cadastre and Land Monitoring, 2021)
This paper approaches urbanization from the broader context of land and economic sciences, with a focus on the theoretical framework and practical use of data classification. International organizations, official government bodies, and private research institutions have different views on urbanization, rely on various methods for statics research and data classification. In this paper we overviewed the term from several angles, such as land use and settlements area, population dynamics and regional economics, agriculture and resources use, followed by sustainable development in the context of urban development plans and policies. The proposed conceptual model of urbanization inland and economics science context determined urbanization as both state and ongoing process. As a result of research work, urbanization process and state key data and research metrics were presented and categorized by fields of application and research subfield category. The important section of the urbanization definition is a robust multistage research framework. We believe that it can help other researchers, as well as the author, look like urban growth, history, and development prospects with less bias and with a focus on long-term vision, multidisciplinary approach. Keywords. urbanization, urban economics, land science, land use, legislation.